Deciphering the therapeutic actions of Brenania brieyi (Rubiaceae) fractions on oxidoinflammatory anomalies - Martins Obinna Ogugofor; Lawrence U S Ezeanyika; Abayomi Emmanuel Adegboyega; Victor Onukwube Apeh; Victor Nwadiogo Ogugua; Florence Nkechi Nworah; Ifeoma Felicia Chukwuma (International Journal of Secondary Metabolite)
A decline in the antioxidant network during the inflammatory response plays a critical role in the pathogenesis of numerous diseases. We designed this study to decipher the therapeutic efficacy of Brenania brieyi in reducing oxidative stress caused by the inflammatory response to cotton pellets. Graded doses of methanol and chloroform fractions of B. brieyi (MFBB and CFBB) and indomethacin were administered to Wistar rats for seven days after implanting sterilised cotton pellets (20 mg). Thereafter, biochemical indices of oxidative stress were determined using blood samples taken through cardiac puncture. Furthermore, molecular interactions, drug-likeness, and toxicity features of B. brieyi phytochemicals were also assessed. Compared with the untreated group, the groups treated with MFBB and CFBB had a significant (p < 0.05) decrease in granuloma tissue weight and MDA levels while increasing glutathione levels, SOD, and CAT activities. In addition, a substantial increase in inflammatory-induced changes in antioxidant nutrients, together with a decline in liver enzymes, was obtained in the treated groups. The docking tests revealed that the top-scoring phytoconstituents of B. brieyi, n-hexadecanoic acid, and 9-octadecanoic acid interacted well with catalase, having docking scores of -6.19 and -7.58 kcal/mol, respectively. Moreover, the hits had good oral drug-likeness features and a safe toxicity profile. The findings of the study provide evidence that B. brieyi has antioxidant and anti-inflammatory properties, suggesting that it could be used as an alternative therapy to regulate oxidative stress-related diseases.